CITRAAN DALAM KUMPULAN SAJAK NYANYIAN KAKI LANGIT KARYA DASRI AL MUBARY - Okta Hari Mulya; Syafrial '; Hermandra ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: This reasearch discusses the imagery in the poetry collection Nyanyian Kaki Langit works Dasri Al mubary. This study used a qualitative approach and descriptive method that aims to describe the images contained in the anthology Nyanyian Kaki Langit Dasri Al Mubary work. In this study the authors used data collection techniques that based on the technical documentation of images in the opinion of Hasanuddin W.S. formulated into conclusion, the results of the research I have found in this study is a six division images in the opinion of hasanuddin W.S. contained in the anthology Nyanyian Kaki Langit Dasri Al Mubary works that include images of sight, auditory imagery, citran smell, feeling imagery, imagery palpation, and motion imagery.Keywords: images, a collection of poems, Nyanyian Kaki Langit, Dasri Al Mubary.